Brazil : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brazil. (IMF Staff Country Reports; Country Report, 2020)
The COVID-19 pandemic has worsened Brazil's longstanding vulnerabilities of low potential growth, high income inequality, and weak fiscal position. While the authorities mounted a rapid and effective response to support the economy and protect the poor and vulnerable, the virus outbreak is yet to be brought under control. Outlook and Risks. Real GDP is projected to contract by 5.8 percent in 2020 followed by a partial recovery to 2.8 percent in 2021. With weak domestic demand, inflation is likely to end 2020 substantially below target. Debt is projected to jump to 100 percent of GDP, due to a 10.6 percentage point deterioration in the primary deficit in 2020, and continue to rise over the next five years. The high level of debt exposes Brazil to confidence shocks. Securing congressional passage of structural reforms to raise potential growth remains challenging.